1D GNR‐PPy Composite for Remarkably Sensitive Detection of Heavy Metal Ions in Environmental Water. Issue 2 (22nd January 2022) - Kulkarni, Bhakti B.; Suvina, V.; Balakrishna, R. Geetha; Nagaraju, D. H.; Jagadish, Kusuma
Abstract: The work reported here exploits the extraordinary features of graphene nanoribbons (GNR) and well‐known conductive polypyrrole (PPy) polymer to develop a very good electrochemically active composite for sensing metal ions. A strong hydrogen bond and π‐π interaction between the two components facilitates an enhanced conductive 3D network that has been used to design and fabricate an electrochemical sensor for selective and sensitive determination of Pb 2+ ions by differential pulse voltammetry (DPV). The probe has been further extended to simultaneously detect Zn 2+, Cd 2+, As 2+, Cu 2+, Pb 2+, Fe 2+ and Hg 2+ ions. Moreover, the larger effective surface area, higher porosity and chelating groups of composite promotes better adsorption‐stripping process of Pb 2+ ions, leading to a high detection limit of 0.03 nM with a sensitivity of 0.7557 μA μM −1 cm −2 . This study is extended to detect heavy metal ions in lake water samples, demonstrating promising applications in real time (environmental) samples, and the study shows a deviation of ≈10 %, when validated with atomic absorption spectroscopy studies. Abstract : Composite of graphene nanoribbons and polypyrrole was developed as an electrochemically active probe for sensing metal ions. The large effective surface area, high porosity and chelating groups of composite led to a high detection limit of 0.03 nM for Pb 2+ ions with a sensitivity of 0.7557 μA μM −1  cm −2 .